KEWENANGAN PEGADAIAN DALAM MENERBITKAN SERTIFIKAT BATU MULIA DI INDONESIA - Alif Arhanda Putra (JURNAL AKTA YUDISIA, 2020)
Abstract Authority of Pegadaian in Issuance of the Certificates of Precious Stones in Indonesia.This research aimed to determine the institution authorized to issue the certificate of the precious stones in Indonesia. This study used the empirical research type to look at the enforcement of the law from the non-legal aspect. The collected data – both primary and secondary data – were analyzed qualitatively. Then, they were described in order to answer the problems of this research.The research results revealed that The authority to issue certificates for the precious stones in Indonesia was given to the authorized and powerful institutes in order to issue certificates for the precious stones in Indonesia, such as the Pawnshop and order private institutes as the actors in the commerce industry of precious stones in Indonesia. Keywords: Authority, The Pawnshop, Certificates of Precious Stones.